Efficacy and Tolerability of Histamine-2 Receptor Antagonist Adjunction of Antipsychotic Treatment in Schizophrenia: A Meta-analysis of Randomized Placebo-controlled Trials - Kishi, T.; Iwata, N. (Pharmacopsychiatry, 2015)
Introduction: No comprehensive meta-analysis has been performed concerning the efficacy and tolerability of adjunctive therapy with histamine-2 receptor antagonists (H2R-ANTs) in schizophrenia patients who were treated with antipsychotics.Methods: Risk ratios, standardized mean differences (SMD), and 95% confidence intervals were calculated.Results: We included 8 double-blinded, randomized placebo-controlled trials (RCTs) (n=418) that met the inclusion criteria (famotidine: N=3, n=74; nizatidine: N=4, n=292; ranitidine: N=1, n=52). Pooled H2R-ANTs were not different from placebo with regard to reduction in overall symptoms and body weight. However, pooled H2R-ANTs resulted in lower body mass index (BMI) than placebo (SMD=−0.68). Moreover, nizatidine was associated with an increase in plasma leptin levels (SMD=− 1.14). There were no significant differences in the discontinuation rates due to all-cause, side effects, and inefficacy between pooled H2R-ANTs and placebo. However, nizatidine produced more depression and dry mouth than placebo.Discussion: H2R-ANT adjunctive therapy did not improve overall symptoms. To clarify the opposite results between body weight and BMI, future research should investigate long-term efficacy and generate more safety data by using larger samples.
Keywords: histamine-2 receptor antagonists; schizophrenia; weight gain; psychopathology; leptin; systematic review; meta-analysis